Gratitude And Happiness Of Adolescents With Single Parents Moderated By Self-Acceptance - Isyatin Rodiyah (Psychological Journal: Science and Practice, 2026)
Happiness in life is something that every human being, including teenagers,really wants . Gaining emotional independence from parents is one of thedevelopmental tasks of adolescents that can affect their level of happiness,especially for adolescents with single parents . This study aims to examinethe effect of gratitude in predicting the happiness of adolescents with singleparents moderated by self-acceptance. Quantitative research with incidentalsampling technique involved 235 subjects with an age range of 13-22 years.The instruments used in this study were the Gratitude Questionnaire Six ItemForm (GQ-6), The PERMA Profiler , and the Indonesian version of ShereerSelf-Accaptance (SSA). Data analysis used moderated regression analysisprocess by Hayes model 1. The results showed that self-acceptance did notmoderate the effect of gratitude in predicting happiness.